The Influence of AI on the Evolution and Facilitation of Remote Work: Beyond the COVID-19 Acceleration - Sood, Vishruti (Digital Repository of Theses, 2025)
As AI technologies continue to be integrated into the remote workspaces, workplace dynamics, productivity, and employee engagement sees a complete transformation. This research examines the part of AI in creating the remote work experience and how these technologies influence efficiency, collaboration and job satisfaction. This study uses a mixed methods research approach using a robust thematic analysis of secondary data to explore trends, challenges and opportunities for AI adoption in virtual workspaces. The main themes are: AI powered task automation; augmentation of virtual communication; and implications for work life balance and employee wellbeing. The research uses a system approach to collecting and analysing data, valuing ethical factors such as participant informed consent, data confidentiality, and observations of data protection procedures. Meaningful insights were derived from secondary data from peer reviewed journals, industry reports and case studies. Themes were coded to identify prevalent patterns and emerging trends to understand in a nuanced way how AI affects different organizational contexts. Results show that AI improves task efficiency and decision making, but comes with issues such as employee adaptability, privacy issues and deskilling. In addition, when it comes to making virtual collaboration tools, AI is playing a key role in minimizing the effect of remote work that leads to loneliness. However, there are gaps in access to AI resources between industries and geographies, which means that technological integration must be equitable. The results indicate the importance of ethical, inclusive, AI deployment for achieving the full benefits of AI while limiting harmful side effects. It finishes by presenting actionable advice to policymakers, companies, and researchers, to capitalise on AI to create productive and sustainable remote work environments. This work makes a contribution to the ongoing discussion about the future of work and provides stakeholders with important insights into how technology and organizational development can intersect.